Pentingnya Pengetahuan Instalasi Sistem Operasi Komputer bagi Mahasiswa Jurusan Kurikulum Teknologi Pendidikan Fakultas Ilmu Pendidikan Universitas Negeri Padang - Meldi Ade Kurnia Yusri (Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2019)
This research was trigerred by the lack of ability to install computer operating systems owned by students. Based on the preliminary study, it was found that only two students of Departement of Curriculum and Educational Technology, Faculty of Education, Universitas Negeri Padang (UNP) in 2015 and in 2016, in the classes of Computer Basics, could do the installation process of a computer operating system before being taught. This study applied a qualitative approach, in which the author attempted to reveal and understand the reality in the field regarding the ability to install computer operating systems that are owned by individual students of the UNP FIP Curriculum and Educational Technology Department. Based on the observations obtained by the author in the field, from 48 students majoring in Curriculum and Educational Technology in 2017, only 7 students were able to complete the computer operating system installation process without errors, installing computer operating systems with errors 16 students and failed computer operating system installations were 25 students.